Lifestyle and pregnancy complications in polycystic ovary syndrome: The SCOPE cohort study. (1st April 2019) - Bahri Khomami, Mahnaz; Moran, Lisa J.; Kenny, Louise; Grieger, Jessica A.; Myers, Jenny; Poston, Lucilla; McCowan, Lesley; Walker, James; Dekker, Gustaaf; Norman, Robert; Roberts, Claire T.
Summary: Objectives: To investigate the risk of pregnancy complications in women with and without polycystic ovary syndrome after consideration of lifestyle factors. Design: Prospective cohort. Patients and measurements: Participants (n = 5628) were apparently healthy nulliparous women with singleton pregnancies from the Screening for Pregnancy Endpoints study in New Zealand, Australia, United Kingdom and Ireland. Multivariable regression models were performed assessing the association of self‐reported polycystic ovary syndrome status with pregnancy complications with consideration of lifestyle factors at the 15th week of gestation. Results: Women with polycystic ovary syndrome (n = 354) were older, had a higher socio‐economic index and body mass index and were less likely to consume alcohol and smoke but more likely to do vigorous exercise and take multivitamins. In univariable analysis, polycystic ovary syndrome was associated with increased risk of gestational diabetes (OR: 2.2, 95% CI: 1.2, 4.0). In multivariable models, polycystic ovary syndrome was only significantly associated with decreased risk of large for gestational age (OR: 0.62, 95% CI: 0.40, 0.98) with a population attributable risk of 0.22%. None of the other outcomes were attributable to polycystic ovary syndrome status. Conclusions: Polycystic ovary syndrome is associated with a lower risk of large for gestational age infants. In this low‐risk population, the risk of pregnancy complications was not increased in women with polycystic ovary syndrome who were following a healthy lifestyle. Further studies are warranted assessing the contribution of lifestyle factors to the risk of pregnancy complications in higher risk groups of women with and without polycystic ovary syndrome.